Fund Advisor Compensation in Closed‐End Funds - Coles, Jeffrey L.; Suay, Jose; Woodbury, Denise (Journal of Finance, 2000)
This paper examines the relation between the premium on closed‐end funds and organizational features of the funds and advisors, including the compensation scheme of the investment advisor. We find that the fund premium is larger when: (a) the advisor's compensation is more sensitive to fund performance; (b) the assets managed by the advisor are concentrated in the fund in question; (c) the advisor manages other funds with low compensation sensitivity to performance and with low concentration of assets managed by the advisor; and (d) the advisor's compensation contract evaluates performance relative to a benchmark.